Biological Control of Fungal Brown Spot Disease in Rice Plants by Streptomyces spp. - Farqad Fathi Hasan (Journal of Global Pharma Technology, 2016)
This study used thirty isolates of streptomycetes were isolated from different locations of soil. All these isolates were subjected for antagonistic test (as biological control agents) against Brown spot fungus Bipolaris oryzae. About 43% of tested streptomycetes isolates gave antifungal activity against Brown spot fungus but 57% of tested organisms did not reveal any antifungal activity. The highest antifungal activity were obtained from two isolates (42 mm and 45 mm), both streptomycetes isolates were identified according to International Streptomyces Project (ISP) based on morphological (macroscopic and microscopic) and physiological characterization as Streptomyces orientalis and Streptomyces exfoliatus.Keywords: Biological control, Streptomyces orientalis, Streptomyces exfoliatus, Bipolaris oryzae, Brown spot disease.